“Professional trading”, exchange rate risk and the growth of international banking: a note - CALLIER, P. (PSL Quarterly Review, 2013)
The movement from fixed to floating exchange rates led to predictions that foreign exchange markets might become more volatile. In particular, the issue whether speculation in the market was stabilising or destabilising was widely debated. Concern was also expressed whether sufficient speculative funds would be available to ensure capital mobility. The author argues that the development of international banking has allowed banks to undertake more speculative foreign exchange trading without incurring greater risk, thus alleviating the problem of capital mobility. JEL: F31, F33, G21